Tantangan Pesantren Dalam Menyeimbangkan Tradisi Dan Modernitas Di Era Kontemporer - Fathatul Lailiyah; Abdul Wahid (Oasis : Jurnal Ilmiah Kajian Islam, 2024)
In the midst of an increasingly modern era, there is a phase of social and cultural transformation in the Islamic boarding schoolÂ  environment, therefore this is a challenge that Islamic boarding schools must face in balancing tradition and modernity in the contemporary era, so Islamic bording schools must not eliminate traditional values which are this is the core identity of Islamic boarding schools even though times have developed rapidly. Especially now that Islamic boarding schools are in the midst of a society that continues to experience change, so it will be difficult to maintain the values contained in Islamic boarding schools. Therefore, students are required to be able to adapt to an increasingly modern and sophisticated world with increasingly modern technology and students can take advantage of this, for example information that would otherwise not be possible to obtain, so to prevent this from happening, students must be able to dig up information that is possible.Â  This information is important to apply in Islamic boarding schools. The aim of this research is to find out how Islamic boarding schools can balance the old traditions that exist in Islamic boarding schools in the current contemporary era. The method used in this research is the tazkiyatun nafs method, and the results of this research are that santri can balance tradition with the challenges of Islamic boarding schools which are supported by the increasing development of technology.